Contact centre culture within and between organisations. - Abramowitz, Brett (My University, 2010)
Organisational culture is an underlying theme in every organisation and moderates an organisation’s success or failure. The employee is a representation of the organisation and it is the congruence of their beliefs with the culture of the organisation that predicts the organisation’s success. Contact centres tend to be the customer- facing department within many organisations but are characteristically distinguished from the rest of the organisation by their use of telephonic communication and stringent performance monitoring. As a result of the critical sales or service interactions that contact centres are responsible for, this research report seeks to establish whether contact centres have a distinct culture or share a common culture with the rest of the organisation. Two contact centres and one administration department were researched in two organisations as well as a single contact centre in a third organisation. The total sample (N=238) allowed the researcher to investigate whether organisational culture varies between contact centres and other divisions within the same organisation or whether contact centres have a shared distinct subculture across organisations. A selfcomposed, 61- item scale entitled “Culture Questionnaire” was used to investigate these differences. Two other minor descriptive scales were included as well as a questionnaire focussing on the South African concept of Ubuntu. The research established that differences in organisational culture exist between departments in different organisations, including contact centres. No differences were established between departments within the same organisations. The results of this research project thus suggest that contact centres do not have a distinguishable subculture and are a representation of the greater organisation.